ANALYSIS OF DEVELOPMENT OF RETURN ON ASSETS (ROA) AND RETURN ON EQUITY (ROE) TO MEASURE FINANCIAL PERFORMANCE IN. SENTOSA RAYA OGAN KOMERING ULU - Wijaya, Rendi (Jurnal Manajemen, 2019)
This study aims to determine how the development of Return On Assets (ROA) and Return On Equity (ROE) to assess financial performance at PT. Sentosa Raya Ogan Komering Ulu. The results of this study indicate that financial performance at PT. Sentosa Raya has been quite good because it has reached racial standards. Good corporate management can be reflected in the financial performance of a company. Development of Return On Assets (ROA) at PT. Sentosa Raya Ogan Komering Ulu from 2013 to 2017 produces an average of 30.87% and has met the standards set above the ratio of 1.5%, the ratio achieved is categorized in the healthy group. The higher the return on the assets produced, the higher the amount of net income generated from each fund embedded in the total assets. While the development of Return on Equity (ROE) in PT .entosa Raya Ogan Komering Ulu during the period of 2013 to 2017 produced an average of 43.50% and met the standards of the industry average of 40%, the ratio achieved showed the condition of the company. pretty good. The higher the results, the better because the dividends that are distributed or reinvested as retained earnings are also getting bigger.